2021
DOI: 10.1155/2021/6661565
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliographic Assessment Using the Degrees of Publication Method: Medicinal Plants from the Rural Greater Mpigi Region (Uganda)

Abstract: In ethnopharmacological research, many field assessment tools exist. Yet, these miss that critical point of how to really determine which species merit the costly lab studies, e.g., evaluation of traditional use via pharmacological assays and isolation of bioactive secondary metabolites. This gap can be filled with the introduction of a new tool for literature assessment: the Degrees of Publication (DoPs). In this study, its application is illustrated through an extensive bibliographic assessment of 16 medicin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 106 publications
0
23
0
Order By: Relevance
“…Despite the widely reported medicinal potential of A. coriaria by ethnobotanical surveys, there are few reports on the phytochemistry and bioactivity of this species [25,36,49]. Classical phytochemical screening of aqueous and organic extracts of A. coriaria stem bark indicated that the active secondary metabolites are saponins, alkaloids, flavonoids, steroids, triterpenoids, reducing sugars, flavone aglycones, volatile oils, polyuronides, glucides, sterols, coumarins, and tannins [50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widely reported medicinal potential of A. coriaria by ethnobotanical surveys, there are few reports on the phytochemistry and bioactivity of this species [25,36,49]. Classical phytochemical screening of aqueous and organic extracts of A. coriaria stem bark indicated that the active secondary metabolites are saponins, alkaloids, flavonoids, steroids, triterpenoids, reducing sugars, flavone aglycones, volatile oils, polyuronides, glucides, sterols, coumarins, and tannins [50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study therefore further add to the scientific basis for their effectiveness in traditional use in the Greater Mpigi region in Uganda as previously described ( Schultz et al, 2020b ). Furthermore, antimalarial activity was studied and verified for the first time for the majority of the species investigated, which was previously determined by the DoP method ( Schultz et al, 2021a ). It needs to be pointed out that only those extracts were selected for antiplasmodial follow-up experiments that acted as hemozoin formation inhibitors in the pre-screen at concentrations of 10 µg/ml or lower.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the n -hexane extract of the leaves (hE005) showed significant quorum quenching activity against the accessory gene regulator ( agr ) system in S. aureus ( Schultz et al, 2020a ). L. calostachys was recently identified using the DoP method as a highly understudied medicinal species that merits further ethnopharmacological and pharmacognostic research in the lab ( Schultz et al, 2021a ). In fact, only three other studies have been published that examine potential bioactive properties of the plant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations